Petrography and Mineral Chemistry of Magmatic and Hydrothermal Biotite in Porphyry Copper-Gold Deposits: A Tool for Understanding Mineralizing Fluid Compositional Changes During Alteration Processes - Idrus, Arifudin (Geological Agency, 2018)
DOI: 10.17014/ijog.5.1.47-64This study aims to understand the petrography and chemistry of both magmatic and hydrothermal biotites in porphyry copper-gold deposits, and to evaluate the fluid compositional changes during alteration processes. A total of 206 biotite grains from selected rock samples taken from the Batu Hijau porphyry Cu-Au deposit was analyzed. Detailed petrography and biotite chemistry analysis were performed on thin sections and polished thin sections, respectively, representing various rocks and alteration types. A JEOL JXA-8900R electron microprobe analyzer (EMPA) was used for the chemistry analysis. The biotite is texturally divided into magmatic and hydrothermal types. Ti, Fe, and F contents can be used to distinguish the two biotite types chemically. Some oxide and halogen contents of biotite from various rocks and alteration types demonstrate a systematic variation in chemical composition. Biotite halogen chemistry shows a systematic increase in log (XCl/XOH) and decrease in log (XF/XOH) values from biotite (potassic) through chlorite-sericite (intermediate argillic) to actinolite (inner propylitic) zones. The y-intercepts on the log (XCl/XOH) vs. XMg and log (XF/XOH) vs. XFe plotted for biotite from potassic and intermediate argillic zones are similar or slightly different. In contrast, the y-intercepts on the log (XCl/XOH) vs. XMg and log (XF/XOH) vs. XFe plotted for biotite from inner propylitic zone display different values in comparison to the two alteration zones. Halogen (F,Cl) fugacity ratios in biotite show a similar pattern: in the potassic and intermediate argillic zones they show little variation, whereas in the inner propylitic zone they are distinctly different. These features suggest the hydrothermal fluid composition remained fairly constant in the inner part of the deposit during the potassic and intermediate argillic alteration events, but changed significantly towards the outer part affected by inner propylitic alteration. High halogen content, particularly Cl, in hydrothermal biotite may portray that copper and gold were transported in mineralizing fluids in the form of chloride complexes CuCl2- and AuCl2-, respectively.